CURRENT GEOPOLITICS AND ITS IMPACT ON RUSSIAN ECONOMY - Ovsanna M. Dzhavadova; Olga S. Linova (Вестник Северо-Кавказского федерального университета)
The item focuses on the unstable economic situation in the post-Soviet area, the economic sanctions against the Russian economy, and their effects for the country and for the region.